(untitled) - Hamilton, William Peter (New York, 1998)
In The Stock Market Barometer, William Hamilton's clear and in-depth analysis explores the Dow Theory's underlying principles, its explanation of averages and its remarkable affinity for predictable cycles of panic and prosperity. More than just a blueprint of the Theory, however, Hamilton's cogent discussion provides a concise examination of the stock market and its history since 1897, as well as thorough descriptions of the notable trends he observed during a distinguished career. His undisputed gifts of insight and interpretation bring focus and flavor to his candid views on a variety of vital topics, including market manipulation, speculation, and regulation.
Keywords: Stock exchanges,Stock price forecasting, Dow Jones industrial average